An evaluation of low-cost wrong-way driving countermeasures at partial cloverleaf interchanges on Kansas interstates - Cunningham, Jack Reid IV (Kansas State University, 2021)
Wrong-way driving (WWD) incidents and crashes continue to be a serious concern for communities across the United States. Wrong-way drivers have been found to typically travel at high rates of speeds, during low light conditions, and on roadways with limited horizontal maneuverability resulting in reduced reaction times. These variables, along with ones that cannot be quantified are likely the reasons wrong-way crashes result in higher rates of fatalities and serious injuries as compared to other traffic crashes. Previous research on WWD includes statistical analyses of crash data, multiple countermeasure comparisons, investigation of driver characteristics, and proposed rewording of the MUTCD. While research has been conducted on countermeasure effectiveness, research has been varied on the type of interchanges evaluated. This study specifically evaluated low-cost countermeasures at partial cloverleaf interchanges in Kansas. Six ramps were selected in the Topeka, KS metropolitan area, including four study sites and two control sites. Three sets of WWD incident data were gathered over a 10 to 14 day period, one before and two after studies, using two sets of pneumatic road tubes on each ramp. Three cases were established to grade the severity of wrong-way incidents based on wrong-entry, self-correction, and error and the results converted to a rate of incidents per 100,000 entering vehicles (ev). The before study found that incident rates ranged from 3.7 to 92 incidents per 100,000 ev. The countermeasures that were selected for evaluations were red retroreflective delineators, oversized and lowered wrong-way signs, and flashing LED wrong-way sign. The first set of after data were collected immediately after installation of the countermeasures and showed improvements at all but one of the study sites with incident rates ranging from 3 to 103 incidents per 100,000 ev. The second set of after data were collected months after installation and showed more improvement at all of the study sites with incident rates ranging from 0 to 40 incidents per 100,000 ev. The study found that the red retroreflective delineators and the oversized and lowered signs were effective in reducing the number and type for WWD incidents; however, the results for the flashing LED sign were inconclusive. Finally, a study was conducted to evaluate the effectiveness of a WWD incident data collection. Multiple sets of pneumatic road tubes were installed at a partial cloverleaf interchange and it was found the proposed data collection methodology indicated the established WWD incident cases were accurate in their representations of the vehicular movements. The study recommended locations for placement of the two primary counters and the use of a third counter.
Keywords: Wrong-way driving; WWD countermeasures; Transportation safety; Traffic engineering; Kansas interstates